A Study on the Comprehensive Evaluation and Analysis of China’s Renewable Energy Development and Regional Energy Development - Liu, Wei; Fan, Wenyu; Hong, Yu; Chen, Chanting (Frontiers in Energy Research, 2021)
The problem of unbalanced energy development in China still exists. How to adjust the energy structure is the key to high-quality economic development in China. This paper analyses the impact of regional energy development levels on high-quality economic development in China from 2016 to 2017, with the global ML methodology and structural equation model. Firstly, from two aspects of environmental and technological factors, the Global Malmquist-Luenberger (GML) production function is used to measure the environmental endowment index of regional energy development in China. Secondly, the evaluation system of China’s energy development is established. The structural equation model is used to measure and evaluate the degree of China’s regional energy development. Combined with the environmental endowment index of regional energy development, the gap between the proportion of regional renewable energy and the optimal energy structure is analyzed. Thirdly, this paper explores the supporting effect of different energy development levels on high-quality economic development. It is concluded that the environmental endowment index of energy development varies among different regions in China, most of which are still underdeveloped, but a few of which have redundant technical elements of renewable energy development. China’s regional energy development model is still dominated by fossil fuel energy, and the proportion of renewable energy driving economic growth is relatively low. Renewable energy can effectively replace the use of fossil fuel energy and have a higher impact on high-quality economic development. Finally, on the basis of the above study, the paper puts forward policy suggestions for Chinese governments to adjust energy structure and promote high-quality economic development.